Evaluation of the Shreveport Predictive Policing Experiment - Hunt, Priscillia (RAND Corporation, 2014)
This report documents an assessment of a predictive policing effort that was conducted to evaluate the crime reduction effects of policing guided by statistical predictions. In addition to a basic appraisal of the process, the report shows the crime impacts and costs directly attributable to the strategy in order to provide a fuller picture for police departments considering if and how a predictive policing strategy should be adopted.